The Effect of Awareness, Knowledge and Tax Sanctions on Taxpayer Motivation - Musda, Muhammad Alqizhaz Faizal; Su’un, Muh.; Sari, Ratna (Newinera Publisher, 2024)
This study investigates the impact of tax awareness, tax knowledge, and tax sanctions on taxpayer motivation in fulfilling their tax obligations. Utilizing quantitative methods, the study finds that both tax awareness and tax knowledge significantly and positively influence taxpayer motivation, while tax sanctions also play an important role. The results show that tax awareness (p = 0.045) and tax knowledge (p = 0.000) contribute to intrinsic motivation, enhancing voluntary compliance by fostering a sense of social responsibility and understanding of taxes' role in national development. In contrast, tax sanctions, while effective in ensuring compliance through deterrence, act more as hygiene factors, promoting minimal compliance. Herzberg’s Motivation Theory supports these findings, highlighting that intrinsic motivator, such as awareness and knowledge, lead to long-term voluntary compliance, while sanctions only ensure basic compliance. The study emphasizes the importance of education and transparency in improving taxpayer understanding and motivation. Policymakers should prioritize initiatives that increase tax knowledge and awareness to cultivate a culture of compliance, rather than solely focusing on punitive measures. Ultimately, enhancing taxpayer motivation through education and awareness programs is critical to fostering sustainable tax compliance.